The dating of the ascension of Agesilaus II to the throne of Sparta and the chronology of the 30th Egyptian Dynasty - Pascual, José (Gerión. Revista de Historia Antigua, 2013)
This paper tries to date the ascension to the Spartan throne of Agesilaus II, one of the most famous and important kings of the Lacedaemonian State, as well as the length of its reign based on both Greek and Latin ancient writers and, specifically, through the Egyptian sources and on what we already know on the chronology of the Egyptian Pharaons of the 30th dynasty. The date on which Agesilaus became king in the Julian Year 399, the Spartan Year 400/399, likewise permits us to establish a more precise chronology of the events that took place in Greece and in the East Mediterranean between 403 and 396 B.C.
Keywords: Ancient History; Greece; 403-396 B.C; Sparta; Agesilaus II.